Dirty Crusty - Barron, Clare (Oberon modern plays., 2019)
'We must be the women of the future standing here in this bathroom because we look like sex and power, we look like sex and power, and you don't even know it, standing there in that motherfucking pantsuit.'Jeanine is determined to improve her life. With sex. With dance. With new hobbies, like horticulture. But self-improvement is hard. Reclaiming your dreams is hard. And personal hygiene is really, really hard.